The rising role of physical activity in multiscale urban aging: evidence from spatial MGWR modeling in Hubei - Junjun Qiu; Yuge Zhang; Binbin Jia; Binbin Jia; Danyang Li; Danyang Li (Frontiers in Public Health)
IntroductionPopulation aging in China exhibits pronounced spatial heterogeneity, driven by complex interactions among demographic dynamics, economic development, healthcare infrastructure, environmental conditions, and lifestyle factors. Understanding which determinants exert the strongest—and most geographically variable—effects is critical for designing targeted healthy-aging policies. This study investigates the multiscale influences on the city-level aging rate in Hubei Province, comparing patterns in 2010 and 2020.MethodsWe applied Multiscale Geographically Weighted Regression (MGWR) to annual data for 17 cities in Hubei. Explanatory variables encompassed demographic indicators (birth rate, mortality rate), economic affluence (per-capita GDP), healthcare infrastructure indicators (quantity of health institutions and service enterprises), environmental measures (per capita urban park green space, centralized treatment rate of sewage treatment plants), and physical activity prevalence. MGWR’s adaptive bandwidth selection enabled each predictor to operate at its optimal spatial scale, while model fit was assessed via AICc, adjusted R2, and residual diagnostics.ResultsIn 2010, spatial variability in aging was dominated by economic (SD≈0.36) and healthcare disparities (SD≈0.31). By 2020, these disparities had largely converged, and demographic divergence—particularly heterogeneous birth-rate effects (SD≈0.42)—became the primary driver. Crucially, physical activity emerged as the most potent local accelerator of aging in 2020 (mean β≈−0.60, SD≈0.25), statistically significant in over half of cities, and operating at a fine spatial scale.DiscussionThe temporal shift from structural inequality to demographic and lifestyle determinants underscores the evolving landscape of population aging. MGWR’s multi-bandwidth approach revealed that physical-activity interventions must be tailored at the city level, while fertility and economic policies warrant regional coordination. These findings demonstrate MGWR’s advantage over global or single-bandwidth models in capturing layered spatial processes. Future research should employ finer spatial units, longitudinal designs, and integrate psychosocial variables to further elucidate healthy-aging pathways.